The Tiberian pronunciation tradition of Biblical Hebrew. including a critical edition and English translation of the sections on consonants and vowels in the Masoretic Treatise Hidāyat al-Qāriʼ 'Guide for the reader' /: including a critical edition and English translation of the sections on consonants and vowels in the Masoretic Treatise Hidāyat al-Qāriʼ 'Guide for the reader'. Volume 2 : (2020) - Khan, Geoffrey
No abstract available